2018
DOI: 10.1007/s12576-018-0594-8
|View full text |Cite
|
Sign up to set email alerts
|

Litter size reduction accentuates maternal care and alters behavioral and physiological phenotypes in rat adult offspring

Abstract: Maternal behavior has a substantial impact on the behavioral, endocrine, and neural development of the pups. This study investigated the effect of altering the neonatal nutritional environment by modifying the litter size on maternal care and anxiety- and fear-like behaviors in rats during adulthood. On postnatal day (PND) 2, litters were adjusted to a small litter (SL) size of three pups per dam or normal litter (NL) size of 12 pups per dam. Maternal behaviors were scored daily during lactation (PND2-21). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Two studies, however, found no differences regarding anxiety‐like behavior (Peleg‐Raibstein et al., 2012; Rincel et al., 2016) and Sasaki et al. (2014) found this behavior to be less prevalent in young offspring (Balsevich et al., 2016; Chen et al., 2008; Dong et al., 2013; Enes‐Marques & Giusti‐Paiva, 2018; Fiorotto et al., 1991; Keesey & Hirvonen, 1997; Lawlor et al., 2007; Leung & Lao, 2000; Oken & Gillman, 2003; Orozco‐Solís et al., 2010; Plagemann, 2005; Sasaki et al., 2014; Tozuka et al., 2009). However, another study by the same author using the same amount of energy from fat and the same behavioral test found a higher prevalence of this behavior in animals at 90 days of life (Sasaki et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, however, found no differences regarding anxiety‐like behavior (Peleg‐Raibstein et al., 2012; Rincel et al., 2016) and Sasaki et al. (2014) found this behavior to be less prevalent in young offspring (Balsevich et al., 2016; Chen et al., 2008; Dong et al., 2013; Enes‐Marques & Giusti‐Paiva, 2018; Fiorotto et al., 1991; Keesey & Hirvonen, 1997; Lawlor et al., 2007; Leung & Lao, 2000; Oken & Gillman, 2003; Orozco‐Solís et al., 2010; Plagemann, 2005; Sasaki et al., 2014; Tozuka et al., 2009). However, another study by the same author using the same amount of energy from fat and the same behavioral test found a higher prevalence of this behavior in animals at 90 days of life (Sasaki et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the litters also may affect body weight (Fiorotto et al., 1991) and behavior (Enes‐Marques & Giusti‐Paiva, 2018). Small litters are associated with over‐nutrition (Chen et al., 2008; Fiorotto et al., 1991) and large litters with under‐nutrition (Fiorotto et al., 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important, as the quality and quantity of maternal care during lactation can impact on offspring behavioral, endocrine and neural development (see review by Curley and Champagne [61]). Specifically, a recent study demonstrated that dams whose litters were reduced to 3 pups (to induce postnatal overnutrition) have improved maternal care, characterize by increased time devoted to arched nursing and licking pups [62]. Not surprisingly the pups had early accelerated growth and were overweight by PN60, as indicated by increased adiposity, and were hyperglycemic and hyperleptinemic [62].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a recent study demonstrated that dams whose litters were reduced to 3 pups (to induce postnatal overnutrition) have improved maternal care, characterize by increased time devoted to arched nursing and licking pups [62]. Not surprisingly the pups had early accelerated growth and were overweight by PN60, as indicated by increased adiposity, and were hyperglycemic and hyperleptinemic [62]. These findings are however difficult to compare directly to the results of the current study where the Reduced litter pups had decreased postnatal growth, which suggests that the extent of litter size reduction in the current study is unlikely to have resulted in improved maternal care.…”
Section: Discussionmentioning
confidence: 99%
“…However, at gestational day 16, females were singly housed and were daily checked (twice a day) for the presence of pups from the outside of the cages. The day of delivery ∼4 h after birth, designated as postnatal day (P0), newborn pups were weighted and litter size was adjusted to 5–6 pups per litter to normalize offspring access to maternal feeding resources and care ( Enes-Marques and Giusti-Paiva, 2018 ). All animals were left undisturbed, except weekly weight measurements and cage changes until euthanasia.…”
Section: Methodsmentioning
confidence: 99%